PERILAKU ORGANISASI DALAM LEMBAGA PENDIDIKAN ISLAM; KAJIAN INTERAKSI ANTARA STRUKTUR , NILAI, DAN KEPEMIMPINAN - Layalil Maghfiroh Zain; Ali Nasith (STKIP Pesisir Selatan, 2026)
This study aims to examine in depth how the relationship between organizational structure, Islamic values, and leadership can shape organizational behavior in Islamic educational institutions. This study is motivated by the fact that many Islamic educational institutions are still struggling to balance professionalism in institutional management with the application of spiritual values. The research was conducted through a literature study method by examining various scientific sources such as books, journals, and previous research results. All data were then analyzed descriptively to find patterns of correlation and influence between the three elements in the context of Islamic education management. The results of the study show that organizational structure acts as a system that regulates the division of tasks and responsibilities, Islamic values become the moral foundation that guides behavior, while leadership acts as a driving force that unites the two so that they run in harmony. When these three elements are harmoniously intertwined, the organizational behavior that emerges is not only efficient but also reflects Islam through attitudes of trustworthiness, fairness, and responsibility. Thus, the balance between structure, values, and leadership becomes the main foundation in building an ethical, productive organizational culture that has spiritual strength in the Islamic education environment.